Influence of Work Ethic on Employee Performance PT. Carsurindo Superintendent - Tumini Sipayung; Roma Sihombing; Amin Hou; Ahmad Fadli; Martin Martin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Research to determine the effect of work ethic on employee performance at PT. Carsurindo Superintendent. This type of research is qualitative research. Jumplah population as much as 78 people and samples using saturated samples as much as 78, data analysis techniques using SEM PLS where the test used is determination test, simultaneous test and hypothesis test. The results showed the results showed that a direct influence on the work ethic variable on employee performance has a path coefficient of 0.879 this indicates that if the higher the work ethic of employees at PT. carsurindo then the higher the performance. The influence has a probability value (p-values) of 0,000 < 0.05, there is a significant influence between work ethic on employee performance at PT. Carsurindo Superintendent.